Integrasi Conway Microdiffusion dan GC-FID pada Penentuan Kadar Alkohol Barang Bukti Forensik Terpadu - Dyah Setyaningrum; Zuffa Anisa; Diah Ayu Setiyaningrum (Universitas Bojonegoro, 2026)
Alcohol analysis of forensic evidence requires analytical methods that provide rapid, accurate, and legally defensible results. This study evaluated the integration of Conway Microdiffusion and Gas Chromatography–Flame Ionization Detection (GC-FID) as a screening–confirmation approach for determining alcohol content in forensic evidence. An applied analytical study was conducted using confiscated illicit alcoholic beverages and blood specimens examined at the East Java Regional Forensic Laboratory. Initial screening was performed using the Conway Microdiffusion method, followed by quantitative confirmation with GC-FID for samples that tested positive. All samples showed positive results during the screening stage. GC-FID analysis identified 49% ethanol and 1% methanol in the illicit alcoholic beverage, while the blood specimen contained 0.0169% ethanol with no detectable methanol. The combined application of both methods provided a systematic analytical workflow in which Conway Microdiffusion served as a rapid preliminary screening tool and GC-FID provided reliable qualitative and quantitative confirmation. This integrated approach improved laboratory efficiency without compromising analytical reliability and may serve as a practical alternative for alcohol examination in forensic laboratories handling routine evidence.